2000
DOI: 10.1148/radiology.214.3.r00mr18755
|View full text |Cite
|
Sign up to set email alerts
|

Arteriographic Detection of Renovascular Disease in Potential Renal Donors: Incidence and Effect on Donor Surgery

Abstract: In this population of potential renal donors, the arteriographic incidence of renovascular disease (10.9%) was higher than previously reported. Although renovascular abnormalities were mild, their detection influenced the plan for donor surgery in almost all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(37 citation statements)
references
References 15 publications
1
34
0
2
Order By: Relevance
“…In a series of 716 potential renal donors for whom 80% of the angiograms were available for retrospective review, 6.6% had FMD. 25 In another series of 1862 patients, 3.8% had angiographic evidence of FMD. 22 A smaller but more recent study confirmed these results.…”
Section: Epidemiologymentioning
confidence: 95%
“…In a series of 716 potential renal donors for whom 80% of the angiograms were available for retrospective review, 6.6% had FMD. 25 In another series of 1862 patients, 3.8% had angiographic evidence of FMD. 22 A smaller but more recent study confirmed these results.…”
Section: Epidemiologymentioning
confidence: 95%
“…Others have suggested that FMD is more common than previously recognized. 5,6,9 The renal arteriograms of 1862 potential renal donors were examined, and FMD was found in 3.8%. 6 A similar prevalence was found in a more recent study of potential kidney donors.…”
Section: Clinical Perspective On P 3190mentioning
confidence: 99%
“…4,5 The mostcommon type of FMD is medial fibroplasia, and because of its benign clinical course, patients with this form of FMD can serve as renal donors. 2,3,6 The American Society of Transplant Physicians has provided guidelines on the suitability of kidney donors; however, there are no clear guidelines on the suitability of potential live-renal donors with asymptomatic FMD.…”
Section: Discussionmentioning
confidence: 99%